Women academics and the changing psychological contract during COVID-19 lockdown - Ronnie, Linda; du Plessis, Marieta; Walters, Cyrill (Frontiers in Psychology, 2022)
This study examines the psychological contract between academics and their institutions during a time of great stress – the COVID-19 pandemic. Given that relationships between these parties have been found to be deteriorating prior to the pandemic, we believed it pertinent to explore how environmental changes brought about through lockdown conditions may have shifted the academic-institution relationship. Through a qualitative research design, our data is from 2029 women academics across 26 institutions of higher learning in South Africa. The major shifts in the psychological contract were found to be workload and pressure, provision of resources, top-down communication, as well as trust and support. Whilst these shifts altered the transactional and interactional nature of the psychological contract, violation, rather than breach, occurred since the emotional responses of participants point to incongruence or misalignment of expectations between academics and their institutions during this time of crisis. We offer recommendations for rebuilding trust and negotiating the psychological contract to re-engage academics in the institution.